Residual vowel reduction to /i/ in functional morphemes in Bantoid - (:unkn) unknown (My University, 2024)
I demonstrate that in many languages of Northern Sub-Saharan Africa vowel qualities of functional morphemes tend to be neutralized through raising, fronting and unrounding towards /i/, similarly to what has been described by Idiatov (2020:65) for the TAM and polarity markers of Greater Manding languages. Typologically, this type of vowel reduction is uncommon both in that it proceeds primarily through raising rather than centralization as in most other languages of the world (cf. Kapatsinski et al. 2020), and that it specifically targets functional morphemes. Within Northern Sub-Saharan Africa, the areal distribution of vowel reduction towards /i/ in functional morphemes is also non-trivial as it is attested in various language families of the area and appears to be absent in the genetically related languages spoken outside of this area.The non-Bantu Bantoid languages and northwestern Bantu languages are situated on the eastern periphery of the area with this kind of vowel reduction where it overlaps with the southwestern part of the Central African interior vowel zone, as defined by Rolle et al. (2020). Languages of the Central African interior vowel zone tend to have phonemic central vowels and reduction through centralization, the latter being the default option typologically. Interestingly, in alignment with their transitional position various Bantoid languages, such as Lamnso’, Mungbam, Isu and Fe’fe’, can be shown to have traces of reduction towards /i/ in functional morphemes as a formerly active phonological process so that the reduction towards /i/ may be described as residual in these languages. The residual status of reduction towards /i/ in functional morphemes in Bantoid languages suggests interesting implications for the history of the region and populations movements, especially when contrasted with the lack of comparable cases of residual reduction towards /i/ on the northern and western peripheries of the area where this kind of
Keywords: African Research